Engagement Practices of Canadian Academic Libraries for the Advancement of Student Voices - Guay, Sarah (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2026)
Objective – Student engagement is an integral part of the mission and function of academic libraries, with powerful potential to impact decision-making across various facets of governance, operations, services, and space design. Despite its importance, however, “student engagement” is a broad and highly contested term, even within the domain of libraries. While recent efforts have been made to categorize the concept of “student engagement” in this context and numerous case studies exist to highlight individual libraries’ efforts, successes, and challenges, there is a lack of existing studies involving a cohesive exploration across Canadian academic libraries. In response to this gap, this research details a national-level investigation of how academic libraries in Canada are approaching student engagement, with specific attention towards use of student voices as a feedback mechanism for decision-making.Methods – Using a combination of a national virtual survey and semi-structured interviews/focus groups with library employees, this study explores specific engagement strategies and processes used by academic libraries, as well as the perceived challenges and benefits of this work.Results – Sample findings indicate that, while library staff are generally enthusiastic about engagement and voice-seeking work, limited time, resources, and complex organizational cultures can limit activities and alienate students. Despite challenges, participants highlighted numerous benefits, including increased proximity and relevance to students, upholding of the key mission and goals of academic libraries, enhanced quality assessment and improvement of library operations through evidence based decision-making, and bolstered ability to pursue authentic equity, diversity, inclusion, and accessibility (EDIA) commitments. Feedback mechanisms, student employment, and teaching and learning interactions were the most reported strategies for engagement, though opportunities for other engagement domains remain.Conclusion – Implications of these findings are discussed in the broader context of library and information science and student engagement literature, followed by recommendations for academic libraries to take action via the integration of user-centred library cultures and co-developed communities/partnerships on campus.